Perancangan User Experience Website Penjualan Batik Madura dengan Pendekatan Human-Centered Design (Studi Kasus: Industri Batik Canteng Koneng) - Rezky Nufahriza; Riswan Septriayadi Sianturi; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Batik is a product that has the potential to be developed in the current era of economic globalization so that several batik industries compete to market their batik to get lots of customers. Canteng Koneng is one of Madura's batik industries that is in great demand by consumers. However, the ordering process at Canteng Koneng is not efficient because it is still done via telephone and Whatsapp. Other problems are also found in the recapitulation process of product data, customer data, and sales data which are still done manually through notes only, without accountancy. The information system website is one of the media for the industry of Canteng Koneng so that it can compete with other batik industries and can help solve the problems. So, to create a website that has an attractive User Interface(UI) and can meet user needs, a User Experience (UX) design is needed. Human-centered design (HCD) is a method that can be used to design UX. In the website that will be designed, there will be features for buyers to view product stock, place orders, and make payments. The features for employees of Canteng Koneng are viewing product data, viewing customer data, and viewing sales data. In order for the design to be according to user requirements, so evaluation of the solution design will be carried out using the usability testing method and the User Experience Questionnaire (UEQ). From the results of the evaluation, there were 5 problems from the aspects of effectiveness, dependability, and perspicuity. Then, make improvements to the results of the evaluation.